IMPACT OF JUDO RULES AMENDMENTS OVER TRAUMA PREVENTION - CHIRAZI Marin (Editura Universitatii Transilvania din Brasov, 2020)
The sport performance can determine the occurrence of trauma that has occurred to me, both in the period I know and that it will be late for me to use some joints. This study would be a good example of the causes of trauma in the prevention of their injuries in a rational approach to the program of learning, consolidation and leadership. This is for the execution of specific technical procedures in competition situations. We have got a comparison of what you have to do at the end of 2019 you will not be and at no you will be until the 23 rd. (U 23) and 2013 before the regulation is amended. They have been monitored in a number of 112 of the most recent events carried out in Bеrgеr, supported by 82 men. From the comparison of the two observations it can be seen a decrease in the number of traumas, either due to the decrease of the fighting time due to the changes in the regulation regarding the fighting time, or due to the change in the score.